Strategi Pelayanan Dalam Meningkatkan Kepuasan Nasabah di PT. Permodalan Nasional Madani Ulamm Syariah Cabang Bangko - Habriyanto Habriyanto; Bambang Kurniawan; Husnul Khotimah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Until now, there are still many who are afraid to start a business, including online business, so a real manifestation of a successful businessman has high self-efficacy/ability in starting a business. Apart from having the ability, a businessman must also be able to understand marketing planning and strategy. well in developing a business so that the business succeeds as expected, therefore the purpose of this research is to find out: 1) How is the self-efficacy of entrepreneurs in online business for FEBI students, 2) What is the strategy for developing entrepreneurship in online business for FEBI students, 3) What are the obstacles faced in developing entrepreneurs in the online business of FEBI students. This type of research is qualitative with a descriptive approach, and the methods used in data collection are observation, interviews and documentation. The subjects in this study were students who had been running their online business for more than 3 years. The number of subjects in this study were 10 people. The results of this study note that FEBI students have high self-efficacy in online business or entrepreneurship, students are confident in their abilities and have expectations for their abilities in doing business online, in building confidence students obtain from several sources, namely personal experience, other people's experiences, verbal persuasion and emotional state. In the student business development strategy it is still not running well and efficiently, and there are obstacles to student businesses such as suppliers, competitors, capital and customers.